PENGARUH PERBANDINGAN TERIGU DAN BUAH LINDUR (Bruguiera gymnorrhiza L.) TERHADAP KARAKTERISTIK DONAT - Swandani, Ni Putu Putri; Widpradnyadewi, Putu Ari Sandhi; Ina, Putu Timur (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 6 No 1 (2017): Jurnal ITEPA, 2017)
The research aims to find out the ratio effect of wheat and lindur fruit to the characteristic of donuts, and to determine the precise ratio between wheat and lindur fruit which can produce donuts with the best characteristic. This Completely Randomized Design (CRD) used in the research with six treatments of ratio between wheat and lindur fruit, namely: 100% wheat and 0% lindur fruit, 90% wheat and 10% lindur fruit, 80% wheat and 20% lindur fruit, 70% wheat and 30% lindur fruit, 60% wheat and 40% lindur fruit, and 50% wheat and 50% lindur fruit. Each treatment was repeated 3 times to obtain 18 experimental units. The result of research showed that the ratio between 80% wheat and 20% lindur fruit resulted in the best donut characteristic with water content of 22.91% (wb), ash content of 1.16% (wb), fat content of 20.73% (wb), protein content of 6.31% (wb), carbohydrate content of 48.90% (wb), improving degree 31.13%, texture rather like and not very soft, flavor like, taste like, not bitter, and not itchy, color like, and overall acceptance like.
Keywords: wheat, lindur fruit, donut